Nothing but the bones - Panowich, Brian (Minotaur Books, 2024)
"In McFalls County, local crime boss Gareth Burroughs runs everything on the mountain. And Nelson "Nails" McKenna has been his enforcer since he was a teenager, though his heart's not really in the dirty work. Then one night in a local roadhouse, Nails goes too far, defending a woman, and even Burroughs's reach can't get him out of this one. With a dead body and countless witnesses, Nails and the woman become fugitives on the run, and unlikely partners. But on the road to Jacksonville, where a possible escape awaits, there's more than one interested party on the pair's trail, and the glimpse they had of getting away scot free suddenly seems elusive. In the end, Nails must make one final stand for his freedom - or pay with both of their lives"--